The Roles of Central Bank Digital Currency over Physical Currency - Aminu Adamu AHMED; Alhaji Adamu SAIDU; Jibril Hussein KAWURE (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2022)
The technology and innovation are the keys used to unlocked impossible imaginations to become possible towards achieving unexpected individual and organizational desired objectives. This study focused on the roles of unprecedented phenomenon called central bank digital currency (CBDC) over physical currency. Initially, the total of 146 articles from various research databases ranging from the year 2018 to 2021 were downloaded. However, 35 articles were reviewed from the total articles downloaded and selected as the study sample size by meeting the title, abstract and contents criteria. Furthermore, the results of this study employed systematic literature review (SLR) to explain in details why CBDC should be chosen and how it supersede the traditional physical currency based on individual and organizational perspectives. The study assesses the roles of CBDC based on three parameters such as features, perceived benefits and challenges of both CBDC and Physical Currency. It also revealed that CBDC can replaces the use of physical currency depends only on how people, businesses perceive the features, benefits (better allocation, accessibility, interest bearing, convertibility and cost reduction) and possible challenges (reverse of the benefits) associated with CBDC compare to it counterpart.